Proposals for a National Health Service - Great Britain. National Health Service
1946-01 1946 1940s 16 pages services as such - medical inspection, the supervision of the health of the child in the school itself, the conduct of special investigations, and the guidance and persuasion of parents, remaining with them. (b) Maternity and child welfare. 16. The care of normal maternity and child welfare - pre-natal and postnatal clinics, child clinics, confinements in the home, etc. - will be the responsibility of the local health authorities, and present powers will be converted into a duty. An important part of this duty will be to make priority arrangements for dental care of mothers and children. The functions of existing welfare authorities which are not county or county borough councils will be transferred to the local health authorities, subject to some delegation of child welfare (para. 18 below). 17. The specialist and institutional aspects of maternity will be in the care of the hospital and specialist service, organised regionally in the manner already proposed. Also to ensure continuity of care, the hospital service will itself provide pre-natal and post-natal clinics for mothers whose confinement takes place in the hospitals. 18. The local health authorities' child welfare functions will be subject to the same kind and degree of delegation - divisional administration within the county area - as the school medical service, so that the care of the children under five at school and not at school can run closely in parallel. (c) Domiciliary midwifery. 19. As part of their maternity functions the local health authorities will be responsible for securing a domiciliary midwifery service for their areas. They will become the local supervising authorities under the Midwives Acts, and the existing supervising authorities which are not county or county borough councils will lose those functions. (d) Health Visiting. 20. Local authorities now provide health visiting services under their maternity and child welfare functions, and local health authorities will continue to do so. But their duties will be enlarged to extend the scope of the health visiting service (particularly from health centres) to include many other types of case to which the health visitor's attention may be drawn by the family doctor service or otherwise. /(e) 292/847/4/83